Integration of Smart Technology and Data Analytics in Vocational Technology Education: A Bibliometric Review and Curriculum Implications - Chairul Anshar; M Giatman; Nizwardi Jalinus; Ernawati Ernawati; Fadhilah Fadhilah; Dedy Irfan; Hansi Effendi (JURNAL HURRIAH: Jurnal Evaluasi Pendidikan dan Penelitian, 2026)
This study aims to clarify contemporary advancements in the incorporation of smart technology into Vocational Technology Education (VTE) and to devise strategic implications for curriculum development. We used a bibliometric analysis and a systematic literature review to look at 128 indexed publications from the Scopus and Web of Science databases that were published between 2015 and 2024. Data were analysed using bibliometric techniques using VOSviewer for keyword network mapping, supported by thematic analysis to generate qualitative insights.The results show that there are three basic conclusions. First, there has been a big increase in the number of publications. Between 2020 and 2024, 73% of studies were published. This is because digital transformation sped up after the pandemic. Second, the discipline is naturally multidisciplinary, with Technology Education (34%), Computer Science (28%), and Engineering Education (22% being the most important areas. Third, keyword analysis finds three main groups of ideas: new ways of teaching and developing the curriculum; using new technologies like AI, IoT, digital twins, and blockchain; and meeting the needs of Industry 4.0/5.0. The report highlights the pressing necessity to recalibrate VTE courses to enhance digital literacy, technical skills, and adaptability. Some of the most important suggestions are to use simulation-based hybrid learning, add digital twin technologies, strengthen triple helix collaboration, and make a long-term plan for digital transformation in vocational education